“O monstro do sertão” : a imagem do nordeste (des) construída na xilogravura de J. Borges - Silva, Luiz César Barbosa da (2021)
This dissertation, focused on the research line “Popular Arts: analytical, pedagogical and creative processes”, addresses the (de)construction of the image of the Northeast in the woodcut “O Monstro do Sertão”, by J. Borges. Resorting to emerging themes such as drought and politics, the artist incorporates in his work relevant issues to understand the formation of this stereotyped image. Thus, we performed a temporal cut of the period in which the print was produced, leading to a discussion on the concepts of Northeast, subordination, place of speech, and decoloniality, concepts that led us to problematize cultural, social, political, and economic aspects of this region. The general objective of this research was to understand if the woodcut “O Monstro do Sertão” (de)constructs a subalternity of the image in the Northeast. In an attempt to answer the question: “does this image constitute a subalternity or not?”, we resort to Burke's (2017) post-Structuralist approach methodology, in which the images are taken as historical evidence. Thus, we conceive the image as an eyewitness, which has its own cultural codes and ways of interpreting reality, with political, social, economic, cultural, and artistic guidelines. In line with this method, in addition to studying the image, we used semi-structured interviews and bibliographic and documentary research as instruments. We divided the research into three sections - The storyteller: from cordel to woodcut, we discuss the trajectory of J. Borges, his origin and visual artistic production; theoretical intersections: we elaborated a study of the several concepts that intertwined in our epistemological discussion and; the image of the Northeast from “Monstro do Sertão”: we generate a debate on aspects such as history, politics, geography, economy, and culture of the Northeast from the engraving and the “O Monstro do Sertão” string. We highlight the contribution of this research with emerging reflections, expanding studies aimed at groups that have historically been silenced or erased. We add that this dissertation is a provocation to construct and deconstruct ourselves as subjects and protagonists of our own history. In the initial formation of the image of the Northeast, the concern was focused on the desires of the dominant elite, which developed mechanisms of domination to remain in the power structure. In contrast to this sense, we evoke the senses that J. Borges's woodcut, “O Monstro do Sertão”, constructs and deconstructs. The study revealed that the threatening being was, in fact, camouflaging the real threats: humanity's actions on the environment and corruption. We also concluded that a more just and humanized society will only be possible through the diversity of subjects, art, culture, and thoughts, valuing the contributions that each person offers to society.